Il simbolismo chimico come interpretazione unificante del mondo materiale scientifico moderno - Villani, Giovanni (Chimica nella Scuola, 2024)
Galileo’s scientific method, Galileo himself tells us, is built on two pillars: sensate esperienze and dimostrazioni necessarie. In modern terms, experiments and mathematical formalization. These two pillars played a fundamental epistemological/scientific role and demarcated natural science from philosophical interpretations at the birth of modern science. The other side of the coin of the Galilean cultural revolution was that this definition of science placed not only all the human and social sciences, but also the entire chemical-biological-medical scientific area outside the scientific boundary. This last area, over a three-century long journey, has built a third scientific pillar centered on chemical symbolism, essential for the modern definition of scientificity. This process of scientific “reappropriation” occurred in the animate, inanimate and in the world of artificial substances. Today we can certainly say that chemistry is the preferred language for a scientific description of matter, whether inanimate or animate, whether natural or artificial. It is to the example of chemical symbolism that the human and social sciences should refer for a complete reunification with the natural sciences.